Determinación de glicemia basal en estudiantes del bachillerato con sobrepeso y obesidad de la Unidad Educativa Atahualpa del año 2014 - López Pesántes, Jairo N. (2014)
Obesity is defined as an excessive accumulation of body fat in the body, children and adolescents gain weight as they grow, since the growth increase the size and volumen of bones, your muscles, and of course, the amount of fat mass.